The English teachers' mastery in TOEFL prediction - Nida Mufidah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2014)
Assessment is often considered as the most important part in instruction. The way of learners taught and the activity carried out in the classroom are greatly influenced by assessment, and the success of a learning program is commonly determined by the result of assessment. This research focuses on the TOEFL test giving the teachers opportunity to prove that they can communicate ideas effectively by simulating classroom and teacher life comunication. This research is then conducted to find out the English teachers’ mastery in TOEFL Prediction in listening comprehension, structure and written expression, and reading comprehension at Junior and Senior High Schools in Kotabaru Regency, South Kalimantan. The research form is a field research by using written test, observation, interview, and documentary technique in collecting data. The subjects of this research were 16 English teachers of Junior and Senior High Schools in Kotabaru Regency, South Kalimantan. The result shows that the teachers’ mastery of TOEFL Prediction in listening comprehension, structure and written expression, and reading comprehension is classified into good category with the mean score 423.06. It recommends English teachers in Kotabaru to apply some different strategies in teaching listening comprehension, structure and written expression, and reading comprehension of each meeting to get high motivation and interest for both teachers and students. Teachers should develop their professions joining some trainings related to English instruction, encourage their students to practice skimming and scanning skill and identify the major poins of the passage, and use the context for vocabulary mastery by listening comprehension and for structure and written expression as well in the teaching and learning through games and fun activities.